Investigation of nanocrystalline CdS/Si diode using complex impedance spectroscopy - El-Gendy, Y. A.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
CdS/n-Si device was fabricated via depositing CdS thin film onto pre-cleaned n-silicon substrates. The atomic force microscope was used to examine the crystal size of the deposited films and its roughness. The AC conductivity and the real part of complex impedance Z' as a function of frequency at different temperatures were studied. The AC conductivity dependence of the applied frequency was explained on the basis of the power law relation. The bulk resistance has been calculated at different temperatures from the complex impedance Z. The temperature dependence of capacitance for CdS/n-Si device at different frequencies was also investigated. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Vapor deposition; Atomic force microscopy; Electrical properties